Acute Hypoxia Suppresses Exogenous Glucose Oxidation, Lowers Fat Oxidation, and Increases Muscle Glycogenolysis During Steady-state Aerobic Exercise (P08-084-19). (24th October 2019) - Margolis, Lee; Wilson, Marques; Whitney, Claire; Carrigan, Christopher; Murphy, Nancy; Radcliffe, Patrick; Gwin, Jess; Young, Andrew; Pasiakos, Stefan
Abstract: Objectives: Lowlanders performing steady-state aerobic exercise during high-altitude (HA) sojourns, hypoxia mediates increased endogenous carbohydrate oxidation compared to sea level (SL). At SL, ingesting carbohydrate during exercise spares endogenous carbohydrate stores and improves endurance. However, it is unclear whether that strategy is effective at HA, as data from a recent study suggests exogenous glucose oxidation is suppressed during aerobic exercise performed 5 hr after arriving at HA. This observation has not been replicated. The objective of this study was to determine substrate oxidative responses to exogenous carbohydrate ingestion during steady-state aerobic exercise at SL and HA. Methods: Using a randomized, crossover design, native lowlanders ( n = 8 males, mean ± SD, age: 23 ± 2 yr, body mass: 87 ± 10 kg, and VO2peak : SL 4.3 ± 0.2 L/min and HA 2.9 ± 0.2 L/min) consumed 145 g (1.8 g/min) of glucose while performing 80 min of metabolically-matched (SL: 1.66 ± 0.14 L/min 347 ± 29 kcal, HA: 1.59 ± 0.10 L/min, 369 ± 39 kcal) treadmill exercise at SL (757 mmHg) and HA (460 mmHg) conditions after a 5 hr exposure. Total carbohydrate and fat oxidation rates (g/min) during exercise were determined by indirect calorimetry, and exogenous, muscle- and hepatic-derived glucose oxidation by tracer technique using breath and blood measurements of 13 C-glucose. Results: Total carbohydrate oxidation was higher ( P < 0.05) at HA (2.15 ± 0.32) compared to SL (1.39 ± 0.14). Exogenous glucose oxidation was lower ( P < 0.05) at HA (0.35 ± 0.07) than SL (0.44 ± 0.05). Muscle glycogen oxidation was higher at HA (1.67 ± 0.26) compared to SL (0.83 ± 0.13). There was no difference in hepatic glycogen oxidation between SL (0.13 ± 0.03) and HA (0.13 ± 0.04). Fat oxidation was lower at HA (0.05 ± 0.07) than SL (0.31 ± 0.08). Conclusions: These data confirm that acute hypoxic exposure suppresses exogenous carbohydrate oxidation during steady-state exercise. Coupled with observations that fat oxidation was reduced and muscle glycogenolysis accelerated in hypoxia, these findings suggest that ingesting carbohydrate during exercise upon acute hypoxia exposure is not an effective strategy for attenuating oxidation of endogenous carbohydrate stores. Funding Sources: Views expressed are the authors and do not reflect the official policy of the Army, DoD, or the U.S. Government. Supported by USAMRMC.